An ultralight charged MOF as fluoro-switchable monitor for assorted organo-toxins: size-exclusive dye scrubbing and anticounterfeiting applications via Tb3+ sensitization. Issue 2 (11th November 2020) - Seal, Nilanjan; Goswami, Ranadip; Singh, Manpreet; Pillai, Renjith S.; Neogi, Subhadip
Abstract : The trifunctional Li(i )-MOF acts as fluoro-switchable sensor for two organo-toxins, invisible-ink based data encrypter and size–specific dye scavenger, where DFT calculations support sensing and adsorption mechanisms considering extended structure. Abstract : The construction of pore-functionalized, charged metal–organic frameworks (MOFs) promises critical fluorosensing of harmful organo-aromatics, toxic pollutant adsorption, and luminescent-ink based anticounterfeiting applications. We report the strategic construction of a non-penetrated framework, CSMCRI-4 (CSMCRI = Central Salt & Marine Chemicals Research Institute), from an electron-rich tricarboxylate ligand and the lightest metal-ion, which possesses anionic [Li2 (COO)4 ] secondary building units (SBUs) and unbound oxygen atom decorated porous channels. The activated MOF (4a ) displays extremely selective and ultrafast luminescent sensing of the lethal 2, 6-dichloro-4-nitroaniline (DCNA) pesticide and the nitrofurazone (NZF) antibiotic with notable quenching and low limits of detection. It is imperative to stress the outstanding reusability of the MOF toward multicyclic sensing of both the organo-toxins. The reversibility of the host–guest interplay between the framework and individual analytes instigates fluorescence "off–on–off" switching, which is demonstrated by handy paper-strip monitoring. Density functional theory (DFT) calculation portrays unprecedented reshuffling of the molecular orbital energy levels in the electron-rich MOF by each nitro-organic, and verifies the framework-analyte supramolecular interactions. The extra-framework cations and free oxygen-atom affixed pore surface benefits selective encapsulation and sensitization of Tb 3+ ions, which sharply change the emission color to green. The blue emission of the pristine MOF and modulated light emission in the Tb 3+ -doped material are utilized as highly regenerable luminescent-inks for vivid acronym encryption. The framework further illustrates charge-exclusive reversible adsorption of the toxic, cationic methylene blue (MB + ) dye through bi-phasic colorimetric variation. DFT calculation precisely delineates the replacement of the pore-occluded guest by MB +, and explicitly validates its pore-fitting induced size selectivity over other dyes.